EFFECT OF SPATIAL DISTRIBUTION OF HORMUZ SALT ON DEFORMATION STYLE IN THE ZAGROS FOLD AND THRUST BELT: AN ANALOGUE MODELLING APPROACH - Bahroudi A.; Koyi H.A. (My University, 2003)
Scaled analogue models of thin-skinned simultaneous shortening above adjacent viscous and frictional decollements simulate the effect of Hormuz salt on the shortening in the Zagros fold and thrust belt. The models consisted of sand layers that partly overlay a viscous layer of silicone and were shortened from one end. Spatial distribution of the viscous decollement varied along strike and dip, as occurs in part of the Zagros fold and thrust belt. In this belt, Phanerozoic sedimentary cover was shortened partly above the Hormuz salt lying on the Precambrian crystalline basement, behaving as a basal viscous decollement. Model results display how the nature of the decollement affects the evolution of an orogenic belt. Using model results, we explain the development of deflection zones, and discuss strain partitioning, formation of different topographic wedges and differential sedimentation along the Zagros fold and thrust belt. Model results suggest the formation of a gentle taper, consisting of both foreward and backward thrusts above a viscous decollement and a relatively steeper taper consisting only of forward-vergent imbricates above a frictional decollement. However, in our models, the steepest wedge with the highest topography formed where the viscous substrate had a limited extent with a transitional boundary (pinch-out) perpendicular to the shortening direction. Shortening of this boundary led to development of frontal ramps associated with significant uplift of the area behind the deformation front.
Keywords: ZAGROS FOLD; PLATE TECTONICS; SEDIMENTS; SALT; CARTOGRAPHY; GEOLOGICAL TIME; Precambrian; Precambrian; Докембрий